Landownership concentration and the expansion of education - Francesco Cinnirella; Erik Hornung (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper studies the effect of landownership concentration on school enrollment for nineteenth-century Prussia. Prussia is an interesting laboratory given its decentralized educational system and the presence of heterogeneous agricultural institutions. We find that landownership concentration, a proxy for the institution of serf labor, has a negative effect on schooling. This effect diminishes substantially in the second half of the century. Causality of this relationship is confirmed by introducing soil-texture to identify exogenous farm size variation. Panel estimates further rule out unobserved heterogeneity. We argue that serfdom hampered peasants' demand for education whereas the successive emancipation triggered a demand thereof.
Keywords: O43; Q15; I25; N33; 330; land concentration; institutions; serfdom; education; Prussian economic history